Respostas

2013-09-01T13:10:57-03:00
A) x² + 2x+4+x=0 > x²+3x+4=0
 (delta)=3²-4*4= 9-16= -7   > não existe resposta
b)3x²-2(x²-2x+1)=3 > 3x²-2x²+4x-2=3 > x²+4x-6=0 (* -1) > -x²-4x+6=0
(delta)= 4²+4*6 = 16+24=40 >   \sqrt{delta} = 2 \sqrt{10}
x = 4+2 \sqrt{10} / -2 = -2- \sqrt{10} 
x'= 4-2 \sqrt{10} /-2 = -2+ \sqrt{10} 

c) x²+ 2/2 - x - 1/3 = 1*1/2 > 6x²+6-6x-2/6 = 3/6 > 6x²-6x-+4-3=0 > 6x²-6x+1=0
(delta)=36-4*6 = 36-24 =12 > raiz de delta= 2
x=6+2/12 = 3+/6 e x'= 3-/6

d) x²/2-x+12/3 = 2x > x²/2-3x+4=0 (*2) > x²-6x+8=0
(delta)=36-4*8=36-32=4 > raiz de delta=2
x=6-2/2=2 e x'=6+2/2=4